Spectroscopic characterization of N = 9 armchair graphene nanoribbons. Issue 8 (3rd July 2017) - Senkovskiy, B. V.; Haberer, D.; Usachov, D. Yu.; Fedorov, A. V.; Ehlen, N.; Hell, M.; Petaccia, L.; Di Santo, G.; Durr, R. A.; Fischer, F. R.; Grüneis, A.
Abstract : We investigate the N  = 9 atoms wide armchair‐type graphene nanoribbons (9‐AGNRs) by performing a comprehensive spectroscopic and microscopic characterization of this novel material. In particular, we use X‐ray photoelectron, near edge X‐ray absorption fine structure, scanning tunneling, polarized Raman and angle‐resolved photoemission (ARPES) spectroscopies. The ARPES measurements are aided by calculations of the photoemission matrix elements which yield the position in k space having the strongest photoemission cross section. Comparison with well‐studied narrow N  = 7 AGNRs shows that the effective electron mass in 9‐AGNRs is reduced by two times and the valence band maximum is shifted to lower binding energy by ∼0.6 eV. In polarized Raman measurements of the aligned 9‐AGNR, we reveal anisotropic signal depending upon the phonon symmetry. Our results indicate the 9‐AGNRs are a novel 1D semiconductor with a high potential in nanoelectronic applications. Abstract : Novel narrow‐bandgap graphene nanoribbons with armchair edges and a width of 9 atoms are studied by a multi‐technique approach. The investigation of core‐level and unoccupied states is performed by X‐ray photoelectron spectroscopy and near edge X‐ray absorption. These experiments are complemented by band structure measurements using angle‐resolved photoemission. Finally, the first experimental data on the polarization dependence of the Raman modes of graphene nanoribbons areshown.